Kedaulatan dan Yurisdiksi Negara terhadap Pulau Buatan dalam Perspektif UNCLOS 1982 - Irfa Ronaboyd (Jurnal Suara Hukum, 2019)
The provisions in UNCLOS 1982 are also historical representations in following developments and demands of the times to solve various problems of sea use. A number of principles in marine law instruments were reaffirmed, in addition to the new principles or provisions added to UNCLOS 1982 in order to resolve future and future maritime territorial disputes. Nevertheless, there are a number of things that have not been regulated in detail by UNCLOS 1982, for example artificial islands.The artificial island discourse was again a concern by various parties, especially international law experts. The debate surfaced after China in the South China Sea built five artificial islands and military installations on it. The artificial island is built on the reefs of the Spartly islands, the South China Sea. Apart from the Chinese polemic in building artificial islands in disputed areas, basically every coastal country has exclusive jurisdiction to build artificial islands within the Exclusive Economic Zone (EEZ). Even under international law all countries have the freedom to build artificial islands on the high seas